Hair Mask Buah Pare Untuk Mengurangi Rambut Rontok Dan Berketombe - Agus Susanti; Lailatun Nasikhah (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2022)
In the current era of globalization, there are many problems with hair loss, dandruff, and unhealthy hair. Hair mask is one of the treatments to treat hair damage. Bitter gourd is known to have a bitter taste and has the benefit of reducing hair loss and dandruff, which is the main ingredient in making hair masks. The purpose of this study was to determine the manufacturing process, application method, and public acceptance of pare fruit hair masks to reduce hair loss and dandruff. The research methods used are literature, experiments, documentation, interviews and questionnaires. Making pare fruit hair mask with composition. stearic acid 20 g, liquid paraffin 40 ml, bitter melon juice 70 ml, menthol 0.5 g, TEA 3.5 ml, lime seed perfume 3.5 ml, nipagin 0.5 g. The use of hair masks is done 2 times a week, the use has been seen after use. The results of the public test to 41 respondents to determine the acceptance of the community. It can be concluded that pare fruit hair mask is effective in reducing hair loss and dandruff as an innovation of pare fruit in making hair masks. Need clinical trials and durability tests of bitter melon hair mask products to reduce hair loss and dandruff. The need for other efforts by diligently washing hair to reduce hair loss and dandruff.